2016
DOI: 10.1016/j.vaccine.2016.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Status of vaccine research and development for Campylobacter jejuni

Abstract: Campylobacter jejuni is one of the leading causes of bacterial diarrhea worldwide and is associated with a number of sequelae, including Guillain-Barre Syndrome, reactive arthritis, irritable bowel syndrome and growth stunting/malnutrition. Vaccine development against C. jejuni is complicated by its antigenic diversity, a lack of small animal models, and a poor understanding of the bacterium's pathogenesis. Vaccine approaches have been limited to recombinant proteins, none of which have advanced beyond Phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…Unfortunately, antibodies directed against these mimics may cross-react with human peripheral nerves, which is the pathogenic basis of GBS. Thus, whole cell oral vaccines that are at times logical for developing protection against other enteric pathogens, are not the preferred approach for vaccine development against Campylobacter (Riddle and Guerry, 2016). Regardless, a whole cell vaccine was developed, but it was unsuccessful in a phase 2b challenge with C. jejuni 81–176 (Tribble et al, 2008).…”
Section: Campylobacter Vaccines For Poultry and Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, antibodies directed against these mimics may cross-react with human peripheral nerves, which is the pathogenic basis of GBS. Thus, whole cell oral vaccines that are at times logical for developing protection against other enteric pathogens, are not the preferred approach for vaccine development against Campylobacter (Riddle and Guerry, 2016). Regardless, a whole cell vaccine was developed, but it was unsuccessful in a phase 2b challenge with C. jejuni 81–176 (Tribble et al, 2008).…”
Section: Campylobacter Vaccines For Poultry and Humansmentioning
confidence: 99%
“…ACE Biosciences developed a protein subunit vaccine that was determined to be non-effective in phase 2b trials (Maue et al, 2014). Another recent study showed that a recombinant non-glycosylated C. jejuni flagellin was poorly immunogenic in Phase I trials and would likely not be effective (Riddle and Guerry, 2016). Schumack et al developed a conjugate vaccine against the Campylobacter capsule polysaccharide (CPS) that conferred 100% protection against diarrhea from a homologous C. jejuni strain in a NHP model (Schumack et al, 2016).…”
Section: Campylobacter Vaccines For Poultry and Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…As a strategically important food-borne pathogen, novel interventions are required to reduce the numbers of campylobacters in the human food-chain. As well as increased bio-security measures, targeted interventions such as poultry vaccines (recently reviewed by Riddle and Guerry, 2016) and the use of specific anti- Campylobacter agents or probiotics (Saint-Cyr et al, 2016) on farm have been proposed, but will require identification of appropriate targets and increased knowledge of C. jejuni physiology respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with C. jejuni infection typically develop mild to severe, bloody diarrhea that may be accompanied by fever. Additionally, several postinfectious disorders have been associated with C. jejuni infection, including Guillain-Barre Syndrome, postinfectious irritable bowel syndrome, and reactive arthritis (2, 3). Further highlighting these concerns is increasing resistance of C. jejuni to the clinically relevant antibiotics azithromycin and ciprofloxacin, prompting the Centers for Disease Control and Prevention to list antibiotic-resistant C. jejuni as a “serious threat” to public health (1).…”
Section: Introductionmentioning
confidence: 99%